2013
DOI: 10.1002/jgra.50459
|View full text |Cite
|
Sign up to set email alerts
|

Magnetospheric electron‐velocity‐distribution function information from wave observations

Abstract: [1] The electron-velocity-distribution function was determined to be highly non-Maxwellian and more appropriate to a kappa distribution, with κ ≈ 2.0, near magnetic midnight in the low-latitude magnetosphere just outside a stable plasmasphere during extremely quiet geomagnetic conditions. The kappa results were based on sounder-stimulated Qn plasma resonances using the Radio Plasma Imager (RPI) on the IMAGE satellite; the state of the plasmasphere was determined from IMAGE/EUV observations. The Qn resonances c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…We note that in a study that appeared after the submission of the present work, Benson et al 45 extended the approach of Ref. 20, setting up a general tool to use the Q n resonances of electron Bernstein waves as a diagnostic for the electron kappa values in space.…”
Section: Discussionmentioning
confidence: 92%
“…We note that in a study that appeared after the submission of the present work, Benson et al 45 extended the approach of Ref. 20, setting up a general tool to use the Q n resonances of electron Bernstein waves as a diagnostic for the electron kappa values in space.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, the Tsallis formalism, which appeared as consequence of using nonadditive entropies, has the distribution function as the main element of the theory (Milovanov & Zelenyi, 2000;Tsallis, 1988Tsallis, , 2009. They have been successfully used, both observationally and theoretically (e.g., Navarro et al, 2015;Pierrard & Meyer-Vernet, 2017;Viñas et al, 2015;Yoon & Livadiotis, 2017), to describe particle distribution functions for velocity or energy (PEDF) 10.1029/2018GL078631 in a number of plasma environments, from the Earth's and other planets magnetospheres (Benson et al, 2013;Kirpichev et al, 2017;Viñas et al, 2005) to solar radio bursts (Cairns et al, 2017). They behave similar to the Maxwellian case for low and central energies but include a power law regime that operates toward higher energies, with a slope determined by the index.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior was much clearer for the electrons, which exhibited ∼ 2 for X ∼ 8R E and seemed to converge to = 4 − 5 for X > 15R E . These results were consistent with Viñas et al (2005) and Benson et al (2013), who found ∼ 2 near the magnetic midnight, in the low-latitude magnetosphere (small Z) near the plasmasphere. In this work we use the GSM coordinate system for the variables X, Y, and Z.…”
Section: Introductionmentioning
confidence: 99%
“…Higher‐order terms will impose an even more restrictive condition on the minimal value of the κ index, and this condition ties κ min to the harmonic number. This is an undesirable restriction on the allowable values of the κ index, since it has been measured to be as low as κ ≃2 both in the solar wind and in the magnetosphere [ Maksimovic et al , ; Štverák et al , ; Benson et al , ]. The result implies that n,κ()α,β(z) could always be represented by a power series, which is not true. As we shall see below, for certain values of the λ index the function has a logarithmic behavior. Even when n,κ()α,β(z) is expressible as a power series, the lowest‐order terms contain a contribution proportional to a power that is not an integer, in general; these terms will also be lacking from the simplifying approach described above.…”
Section: Special Functions For Kappa Plasmasmentioning
confidence: 99%
“…Higher-order terms will impose an even more restrictive condition on the minimal value of the index, and this condition ties min to the harmonic number. This is an undesirable restriction on the allowable values of the index, since it has been measured to be as low as ≃ 2 both in the solar wind and in the magnetosphere [Maksimovic et al, 1997;Štverák et al, 2009;Benson et al, 2013].…”
Section: The Kappa Gyroradius Functionmentioning
confidence: 99%